2009
DOI: 10.1016/j.physa.2009.03.036
|View full text |Cite
|
Sign up to set email alerts
|

The ground state energy of the Edwards–Anderson spin glass model with a parallel tempering Monte Carlo algorithm

Abstract: We study the efficiency of parallel tempering Monte Carlo technique for calculating true ground states of the Edwards-Anderson spin glass model. Bimodal and Gaussian bond distributions were considered in two and three-dimensional lattices. By a systematic analysis we find a simple formula to estimate the values of the parameters needed in the algorithm to find the GS with a fixed average probability. We also study the performance of the algorithm for single samples, quantifying the difference between samples w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 42 publications
5
53
1
12
Order By: Relevance
“…It is well known that finding the GS of spin glass system in D = 3 is an NP-complete problem [59,60] and there exist a large number of heuristic algorithms developed in order to tackle this outstanding problem [60][61][62][63][64]. In a recent paper, Roma et al [37] have concluded that PT is comparable to the performance of the more powerful heuristics. In particular, they have concentrated on the estimation of the minimum number of PTSs needed to achieve a true GS with a given probability.…”
Section: Ground States Of 3d Spin-glass Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that finding the GS of spin glass system in D = 3 is an NP-complete problem [59,60] and there exist a large number of heuristic algorithms developed in order to tackle this outstanding problem [60][61][62][63][64]. In a recent paper, Roma et al [37] have concluded that PT is comparable to the performance of the more powerful heuristics. In particular, they have concentrated on the estimation of the minimum number of PTSs needed to achieve a true GS with a given probability.…”
Section: Ground States Of 3d Spin-glass Modelsmentioning
confidence: 99%
“…We note that, due to some differences in defining the PTS, our notation is not identical with that in Ref. [37], but the analogies are obvious and we will also use N s to denote the number of different samples. The collapse example in Fig.…”
Section: A Ground States Of the 3d Eab Model: Further Tests Of Pt Prmentioning
confidence: 99%
“…17,18 Recently, we have shown that this technique is a powerful heuristic method for reaching the GS of the EAB model up to L = 30 in 2D and L = 14 in 3D. 19 As in the RLSA many independent runs of parallel tempering are needed, we have obtained the RL of samples up to L = 18 in 2D and L = 9 in 3D. Parameters used here are the same as in Ref.…”
Section: Model and Algorithmmentioning
confidence: 99%
“…Parameters used here are the same as in Ref. 19 and n = 10 independent runs were carried out in all the cases.…”
Section: Model and Algorithmmentioning
confidence: 99%
“…For the systems with (J 1 , J 2 ) couplings and vacancies, sufficiently large system sizes are required in order to find the true groundstate among numerous possible magnetic configurations. For this purpose, the parallel tempering technique based on Monte Carlo method, which was applied in studying spin glass systems [48], is an appropriate approach. Once the groundstate is determined, the magnetic order-disorder phase transition at finite temperatures can be investigated by large-scale Monte Carlo simulations.…”
Section: Introductionmentioning
confidence: 99%